The Synergistic Effects of Pyrotinib Combined With Adriamycin on HER2-Positive Breast Cancer - Wang, Chaokun; Deng, Shuzhen; Chen, Jing; Xu, Xiangyun; Hu, Xiaochen; Kong, Dejiu; Liang, Gaofeng; Yuan, Xiang; Li, Yuanpei; Wang, Xinshuai (Frontiers in Oncology, 2021)
Pyrotinib (PYR) is a pan-HER kinase inhibitor that inhibits signaling via the RAS/RAF/MEK/MAPK and PI3K/AKT pathways. In this study, we aimed to investigate the antitumor efficacy of pyrotinib combined with adriamycin (ADM) and explore its mechanisms on HER2+ breast cancer. We investigated the effects of PYR and ADM on breast cancer in vitro and in vivo. MTT assay, Wound-healing, and transwell invasion assays were used to determine the effects of PYR, ADM or PYR combined with ADM on cell proliferation, migration, and invasion of SK-BR-3 and AU565 cells in vitro. Cell apoptosis and cycle were detected through flow cytometry. In vivo, xenograft model were established to test the effect of PYR, ADM, or the combined therapy on the nude mice. Western blotting was performed to assess the expression of Akt, p-Akt, p-65, p-p65 and FOXC1. The results indicated that PYR and ADM significantly inhibited proliferation, migration and invasion of SK-BR-3 and AU565 cells, and the inhibitory rate of combination group was higher than each monotherapy group. PYR induced G1 phase cell-cycle arrest, while ADM induced G2 phase arrest, while the combination group induced G2 phase arrest. The combined treatment showed synergistic anticancer activities. Moreover, PYR significantly downregulated the expression of p-Akt, p-p65 and FOXC1. In clinical, PYR also exerts satisfactory efficacy against breast cancer. These findings suggest that the combination of PYR and ADM show synergistic effects both in vitro and in vivo. PYR suppress the proliferation, migration, and invasion of breast cancers through down-regulation of the Akt/p65/FOXC1 pathway.